Indications of Labor Induction at Delivery Room of Maternity Teaching Hospital in Erbil City - Bewar Husamaldeen Salihi; Awaz Aziz Saeed (Hawler Medical University, 2021)
Background and objectives: Induction of labour means stimulation of contractions before the birth starts spontaneously, with or without ruptured membranes. The most common indications include oligohydramnios, pre-labour rupture of the membranes, high blood pressure during pregnancy, severe fetal growth restriction, post-term pregnancy, and various maternal medical conditions such as chronic hypertension and diabetes. The aim of the study was to find out the different indications of labour and associated obstetrical factors in a local tertiary hospital. Methods: A cross-sectional study was conducted among 120 parturient women who attended a delivery room in the Maternity Teaching Hospital in Erbil City from the period of 2nd June to 2nd October 2020. After reviewing the literature, a questionnaire was prepared to obtain socio-demographic data, data related to reproductive characteristic and data related to the indications for labour induction. The data were analyzed using descriptive and inferential statistical approaches. Results: The study included 120 patients with the highest percentage of the patients (49.1%) were 16 to 23 years old and more than half of the sample (51.6%) had a post-term pregnancy, gestational hypertension and pre-eclampsia (15%). There were highly significant statistical differences between parity, gestational age and indication of labour induction, and significant differences between gravidity and antenatal care visits and indications for labour induction. Conclusions: The majority of the sample had a post-term pregnancy of 40 and 42 weeks as an indication for induction of labour followed by gestational hypertension and pre-eclampsia, oligohydramnios and pre-labour rupture of membrane. There was a statistically significant difference between the antenatal care visit and parity with the induction of labour.